Analytical Characterization and Comparison of Tristyrylphenol Ethoxylates Used in Agrochemical Formulations. Issue 2 (10th December 2014) - Glaubitz, Johannes; Schmidt, Torsten C.
Abstract: Tristyrylphenol ethoxylates are a group of technical nonionic surfactants that contain no single defined molecule but have a polymeric distribution with an average of 3 styrene and 16 ethylene oxide units. To analyze differences in the ethylene oxide distribution of the surfactant from various suppliers, and thus to specify more precisely the required quality for its use in agrochemical formulations, an analytical method was developed using liquid chromatography coupled to time‐of‐flight mass spectrometry with exact mass measurement in combination with multivariate data analysis. The method investigated here enables a fast and comprehensive characterization and comparison of the tristyrylphenol ethoxylates from different sources. The batches showed significant differences among suppliers with regard to composition and content of by‐products. Differences include the content of the different styrenated phenol ethoxylates (e.g., mono‐, di‐, tri‐, and tetrastyrylphenol ethoxylates) and of mono‐ and distyrylphenol copolymerized propoxylates–ethoxylates. The supplier of a given sample could be traced based on these differences by using a combination of principal component analysis and hierarchical clustering analysis. This was possible using either the raw material or a model agrochemical formulation containing the surfactant.